Identification and Ethno-botanical survey of medicinal plants in Vathalmalai hills, Eastern Ghats, Dharmapuri district, Tamilnadu, India - S, Loganathan; K, Selvam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Identification and ethnobotanical survey was made on the utilization of medicinal plant the tribal community of Vathalmalai Hills in Dharmapuri, Tamil Nadu, India. The objective of the study was to identify and documented the medicinal plants traditionally used by tribal people. Methods: The study was conducted from October 2016 to October 2017. The data were collected from local tribal community, they were interviewed using semi-structured questionnaires, and their traditional ethnomedicinal knowledge was recorded. As, we had collecting the information through local tribal peoples, they we are know the plant local names as well as which plants and parts are mostly used in various disease and disorders problems. Results: A total of 82 plant species and belonging to 40 families were identified. They are most frequently used plant parts leaf and most of the medicine prepared in the form powder and paste. The important disease cure for cold, diarrhea, chicken pox, smallpox, cough, headache, and stomach ache. Conclusion: The ethnomedicinal survey of medicinal plants recommended by traditional healers for the treatment of various disease and disorders new areas of research on the antihypertensive effect of medicinal plants. In the case of safety and effectiveness, they can be refined and processed to produce natural drugs.